Efficacy and Response Biomarkers of Apatinib in the Treatment of Malignancies in China: A Review - Tian, Zhichao; Niu, Xiaohui; Yao, Weitao (Frontiers in Oncology, 2021)
Apatinib is a multitarget tyrosine kinase inhibitor marketed in China for the treatment of advanced gastric cancer (GC) and hepatocellular carcinoma (HCC). It has also been used off-label for the treatment of many other malignancies. To comprehensively evaluate the efficacy of apatinib as a targeted therapy in the treatment of malignancies, we conducted systematic online and manual searches of the literature on apatinib in the treatment of malignancies. In this review, we first summarized the efficacy of apatinib against various malignancies based on clinical trials where results have been reported. In prospectively registered trials, apatinib has been proven to be effective against GC, HCC, lung cancer, breast cancer, sarcoma, esophageal cancer, colorectal cancer, ovarian cancer, cervical cancer, cholangiocarcinoma, diffuse large B-cell lymphoma, nasopharyngeal carcinoma, and differentiated thyroid cancer. The response biomarkers for apatinib were also reviewed. This review will serve as a good reference for the application of apatinib in clinical studies and the design of clinical trials.